Up-conversion properties of lanthanide-organic frameworks and how to track ammunitions using these materials - Weber, Ingrid T.; Terra, Idelma A. A.; de Melo, Adenaule J. G.; Lucena, Marcella A. de M.; Wanderley, Kaline A.; Paiva-Santos, Carlos de O. [UNESP]; Antonio, Selma G. [UNESP]; Nunes, Luiz A. O.; Paz, Filipe A. A.; de Sa, Gilberto F.; Junior, Severino A.; Rodrigues, Marcelo O. (Royal Soc Chemistry, 2012)
This manuscript reports the first example of up-conversion properties involving Yb3+ and Tb3+ ions in five isostructural Lanthanide-Organic Frameworks (LnOFs), herein designated as UCMarker-1 to UCMarker-5, respectively, and their application as optical probes for the identification of gunshot residues (GSRs) and the ammunition encryption procedure. The excitation of the Yb3+2 F-7/2 <-> F-2(5/2) transition (980 nm) at room temperature leads to visible up-conversion (UC) emission of Tb3+ D-5(4) -> F-7(J). The GSR and lead-free primer residues are easily identified upon UV radiation (lambda = 254 nm). These results prove that the exploration of LnOFs to identify GSR is attractive for the identification of ammunition origins or caliber recognition.